Prevalence of Chronic Kidney Disease in Meghalaya, India: A Retrospective Study - Marbaniang, Kathrina; Hynniewta, Barry Cooper; Kharkrang, Cordilia; Sayoo, Susa Teidaka; Phanjom, Probin (Asian Journal of Biological and Life Sciences)
Objectives: To evaluate the prevalence of chronic renal disease in patients attending a tertiary care hospital in Meghalaya, India. Materials and Methods: A retrospective study was carried out in the dialysis unit of Civil Hospital in Shillong between January 2, 2017, and July 11, 2024, to gather data on the patients undergoing dialysis treatments. The study involved 15+ individuals with Chronic Kidney disease and Acute Kidney Injury from urban and rural areas, who regularly received dialysis at Civil Hospital from January 2017 to July 2024. The data was analyzed using Microsoft Excel, categorizing patients into age and gender groups, and presented in tables and bar graphs. Results: This study examined 10221 dialysis cycles of patients with Kidney Disease at Civil Hospital, with CKD being the most common. Gender distribution was male, age group, urban/ rural location, and 2023 saw the highest spike. Conclusion: The study reveals that Chronic Kidney Disease (CKD) prevalence increases with age, particularly among males/females, and suggests lifestyle changes, early detection, and management strategies can reduce its progression.
Keywords: Chronic Kidney Disease (CKD); Dialysis; Diabetes Mellitus; Prevalence.